Cell growth, global phosphotyrosine elevation, and c-Met phosphorylation through Src family kinases in colorectal cancer cells. - Emaduddin, M; Bicknell, D; Bodmer, W; Feller, S (2008)
The heterogeneity of cancer cell signaling is a significant obstacle for the effective development and clinical use of molecularly targeted therapies. As a contribution to a better understanding of the diversity of signaling activities in colorectal cancers (CRCs), we have analyzed the activity of Src family kinases (SFKs), which are implicated in human cancer development, in 64 CRC cell lines. A striking diversity of SFK activity was observed within this panel. Importantly, all CRC lines tested depend on SFK activity for their growth. In addition, SFK activity levels strongly correlated with global levels of tyrosine-phosphorylated (pTyr) proteins in CRC lines. SFK inhibition substantially reduced these pTyr levels, suggesting that SFKs may function as signal integration points and master controllers for the pTyr protein status in CRC lines. The majority of analyzed CRC lines with high-SFK activity express activated c-Met (pYpY1234/1235), a receptor tyrosine kinase contributing to the regulation of cell proliferation, migration, and invasion. Inhibition of SFKs reduced c-Met phosphorylation in most cases, indicating a reversed signal flow from SFK to c-Met. We conclude that SFK activity is important for the growth of CRC lines, although only low activity levels are required. If this also is true for CRC patients, tumors with low-SFK activity may be particularly sensitive to SFK inhibitors, and such patients should be targeted in clinical trials testing SFK inhibitors.